SOCIAL ENTREPRENEURSHIP: DEFINING THE CONCEPT AND KEY COMPONENTS - VĂDUVA CONSTANTIN-DANIEL (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
Social entrepreneurship represents a transformative approach to business, combining entrepreneurial principles with a commitment to social good. It differs from traditional entrepreneurship by prioritizing social value over profit. Social entrepreneurship integrates economic viability with a commitment to solving societal challenges. This paper examines the definition and essential components of social entrepreneurship, which include a social mission, innovation, financial sustainability, and scalability. To this ends, the author employed a qualitative research method. Drawing from theoretical perspectives such as stakeholder theory, triple bottom line, and institutional theory, the results of the study provide a comprehensive understanding of how social entrepreneurs innovate to address social issues. Also, they show the hybrid nature of social entrepreneurship, positioned at the intersection of the for-profit and non-profit sectors.